PID control education for computer engineering students: A step to bridge a cultural gap. (30th June 2019) - Leva, Alberto
Abstract: In computer engineering curricula, control is typically taught only to students willing to specialise in embedded systems, real-time, and the like. Nowadays, this is becoming a problem. Control-based techniques are gaining importance as a means to manage, optimise and also design computing systems. In such a scenario, a lack of control culture is critical. However, a computer engineering curriculum may not have the time and space to introduce a suitably tailored but "complete" course on the principles of systems and control. This paper proposes a solution, based on a PID-centred activity, where the occasion is taken to introduce and stress selected general ideas.